Etika Jurnalisme Televisi di Tengah Disorientasi Negara dan Pasar - Siregar, Ashadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2003)
Indonesia is currently in a serious trouble as public sphere which used to be dominated by the state and currently occupied by the market in order to satisfy the business. The barriers for institutionalize freedom of press for democratizing Indonesia not only appear from the way the state exercise its power but also from the bussines work in the market. In order to solve that problem, the author suggests that developing a strong and independent ethics of journalism is a strategic, yet difficult challenge to be met by journalist community. The challenge essentially is not merely to make sure that the ethics match with the interest of the bussinesses in maximising their profit and to match the interest of the state in making use of coercion, but also to make them culturally compatible.